Investigating Usability Guidelines in Developing Mobile Application - Mohammed, Siti Asma; Abd Aziz, Nor Azah; Ariffin, Asma Hanee (Journal of ICT in Education, 2019)
The extensive use of smart phones has become an increasingly trend in promoting and disseminating the sharing of information. Use of smart phone is also widely in use among university students to help them in term of education, time management, and access of information. However, numbers of mobile application for public universities in Malaysia is still low. Usability has been recognized as a significant quality dimension to determine the success of information sharing among the mobile phone users. Usability has become the key factor for successful use of mobile applications especially for those who have limited experiences with new technology. User expectations are the most basic thing in designing mobile applications. Therefore, the selection of the best guidelines should be taken into considerations in determining the usability aspects in the early design phase of the application. Nevertheless, there is still lack of structured guidelines that are available from the literature of mobile applications development. Thus, this article reviews some existing studies to investigate the best usability guidelines available in developing mobile application for public universities in Malaysia. This review will help researchers and practitioners to create more usable applications that meet the user expectations especially in the university environment.